Saba Hassan - Thesis submitted in partial fulfilment of the degree of Doctor of Clinical Psychology (DClinPsych) - Hassan, S (2023)
Systematic reviewObjectives: This systematic review focuses on neuropsychological outcomes in school-aged children (5-17yrs old) with a confirmed diagnosis of non-syndromic craniosynostosis (NSC). Methods: PsycINFO, PubMed & CINAHL, and reference lists of previous reviews were searched until March 2023. Inclusion criteria: Standardised neuropsychological tests, were performed on children between the age range of 5-17 years old, and quantitative data was available. Two raters were used for screening, eligibility, extraction, and quality assessment. Results: 18 eligible studies were included in this systematic review. The quality of studies was mixed, with n=7 “strong”; n=5 “moderate”; n=6 “weak”. Data indicated that children with sagittal, metopic and Unicoronal NSC were not significantly different in Full Scale Intelligence Quotient (FSIQ) and specific cognitive domains in comparison to controls. Sagittal NSC patients most consistently demonstrated no difference in cognitive profile from the general population. For metopic patients, some studies showed a more uneven cognitive profile. Unicoronal focussed studies showed cognitive differences between left/right sides. However, these two sub-types had lower sample sizes in general. Discussion: Overall, evidence to date indicates children with NSC are performing similarly to controls, with some differences between suture sub-types. Higher quality research studies are needed to draw reliable conclusions regarding outcomes in this population. However, there is an improvement in quality since 2015. The biological, developmental, and environmental factors that may mediate the results are discussed. Finally, recommendations are made to future researchers for acknowledgments of bias, improved methodological quality and directing research toward those in hard-to-reach populations.